Evaluación del rendimiento del cultivo de pimiento (Capsicum anuum L.) bajo tres niveles de fertilización química y tres distanciamientos de siembra - Endara Lagos, Silvia Alexandra (2017)
SUMMARY This research was conducted at the El Aguacate community, Monte Olivo parish, Bolivar Canton, Carchi province with the following geographical coordinates: North latitude: 0 ° 20' 00 "west longitude: 77 ° 48' 00" at an altitude of 2 500 meters In order to evaluate the proper planting densities for cultivation and fertilization optimum level to improve the yield and production of the crop. The experimental design of randomized complete block was used in factorial arrangement (A x B), regarded as Factor A planting densities and Factor B levels of chemical fertilization. Variables were evaluated; plant height, stem diameter, height to the insertion of the first wishbone, days to flowering, number of commercial fruits, performance categories and economic analysis models performed treatments. The experimental results showed that: treatment , seeding 0.30 x 0.80 m with means fertilization record higher averages in the variables; plant height, stem diameter, number of commercial fruits, performance categories (first), treatment, seeding 0.30 x 0.80 m with fertilization alta, obtained highest average in; performance by category (third), and total yield, also had the highest economic profit of 16,038.30 USD / ha confirming that the crop responded better to the high fertilizer application and planting densities 0.30 x 0.80 m where the greatest agronomic performance of the plant, production increased economic profit of 16,038.30 USD / ha, followed by seeding 0.15 x 0.80 m with fertilization alta with 15,365.06 USD / ha appreciated .